Assessment and causes of stridor. (March 2016) - Pfleger, Andreas; Eber, Ernst
Summary: Stridor is a variably pitched respiratory sound, caused by abnormal air passage during breathing and often is the most prominent sign of upper airway obstruction. It is usually heard on inspiration (typically resulting from supraglottic or glottic obstruction) but also can occur on expiration (originating from obstruction at or below glottic level and/or severe upper airway obstruction). Stridor due to congenital anomalies may exist from birth or may develop within days, weeks or months. Various congenital and acquired disorders prevail in neonates, infants, children, and adolescents, and have to be distinguished. History, age of the child and physical examination together often allow a presumptive diagnosis. Further investigations may be necessary to establish a definite diagnosis, and flexible airway endoscopy is the diagnostic procedure of choice in most circumstances ("stridor is visible").